2017
DOI: 10.7150/ijms.19229
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of Dolichoarteriopathies of the Internal Carotid Artery: A Review

Abstract: Dolichoarteriopathies of the internal carotid artery (DICAs) are not uncommon, and although several studies have investigated DICAs, several questions regarding the etiology and best management course for DICAs remain unanswered. It is also difficult to correlate the occurrence of DICAs with the onset of clinical symptoms. Therefore, we surveyed the literature in PubMed and performed a review of DICAs to offer a comprehensive picture of our understanding of DICAs. We found that DICAs can be classified into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 86 publications
1
37
0
10
Order By: Relevance
“…Среди причин данного явления выделяют разнообразные процессы дегенерации позвоночника, ведущие к «укорачиванию» шейного отдела: физиологическая деструкция межпозвоночных дисков, патологическая деструкция (болезнь Бехтерева и т.д.). Другими причинами приобретенной извитости являются метапластическая трансформация, слабость соединительной ткани, а также увеличение диаметра бифуркации ОСА в результате возрастной деградации и фрагментации внутримышечного эластина [18]. Таким образом, изменяется кривизна и формируется долихоартериопатия ВСА, что приводит к гемодинамическим перестройкам в данной области даже после КЭЭ [18,19].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Среди причин данного явления выделяют разнообразные процессы дегенерации позвоночника, ведущие к «укорачиванию» шейного отдела: физиологическая деструкция межпозвоночных дисков, патологическая деструкция (болезнь Бехтерева и т.д.). Другими причинами приобретенной извитости являются метапластическая трансформация, слабость соединительной ткани, а также увеличение диаметра бифуркации ОСА в результате возрастной деградации и фрагментации внутримышечного эластина [18]. Таким образом, изменяется кривизна и формируется долихоартериопатия ВСА, что приводит к гемодинамическим перестройкам в данной области даже после КЭЭ [18,19].…”
Section: Discussionunclassified
“…Другими причинами приобретенной извитости являются метапластическая трансформация, слабость соединительной ткани, а также увеличение диаметра бифуркации ОСА в результате возрастной деградации и фрагментации внутримышечного эластина [18]. Таким образом, изменяется кривизна и формируется долихоартериопатия ВСА, что приводит к гемодинамическим перестройкам в данной области даже после КЭЭ [18,19]. В проведенном нами исследовании была установлена динамика нарастания извитости ВСА по данным ЦДС, что подтверждает вышеизложенную теорию, которая в свою очередь свидетельствует о влиянии геометрии сосудов на физиологичность кровотока и процессы рестенозирования.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…2,3 It has been suggested that CAT is an arterial adaptive response due to smooth muscle and endothelial proliferation and migration. 4 Arteries with tortuosity exhibit elastin degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…9 Hemodynamic models have shown the possibility of ischemia due to tortuosity of arteries. [10][11][12] In clinical studies, carotid artery tortuosity was associated with brain and eye ischemia, 4,13 and CAT has been linked to myocardial ischemia. 8,14,15 In the noninvasive evaluation of CAT patients for ischemia, higher rates of positive stress echocardiography test have been found.…”
Section: Introductionmentioning
confidence: 99%